A Cross-Sectional Survey to Measure the Prevalence of Chronic Pulmonary Aspergillosis (CPA) Complicating Pulmonary Tuberculosis in Northern Uganda. (4th October 2017) - Page, Iain; Hosmane, Sharath; Onyachi, Nathan; Opira, Cyprian; Opwonya, John; Richardson, Malcolm; Sawyer, Richard; Sharman, Anna; Denning, David
Abstract: Background: Chronic pulmonary aspergillosis (CPA) complicates pulmonary tuberculosis (TB). It has a 5-year mortality of up to 85%, but is treatable with itraconazole or surgery. The estimated global prevalence of CPA post-TB is 0.8–1.3 million cases. We conducted the first survey to measure the prevalence of CPA secondary to pulmonary TB. Methods: A cross-sectional survey of adults treated for pulmonary TB within the last 7 years in Gulu, Uganda. All underwent clinical assessment, chest X-ray and Aspergillus -specific IgG measurement by Siemens Immulite at a cut-off of 20mg/L, which has a sensitivity of 93% and a specificity of 98% for CPA diagnosis. Patients were resurveyed two years later. CT scan was performed in those with positive serology or chest X-ray signs of CPA. GeneXpert TB PCR testing was performed on those with productive cough. CPA was diagnosed in patients with ALL of the following; (1) >1 month cough or haemoptysis, (2) raised Aspergillus -specific IgG, and (3) paracavitary fibrosis, aspergilloma or progressive cavitation on imaging. Simple aspergilloma was diagnosed in asymptomatic patients with aspergilloma and positive serology. Results: In total, 400 patients were recruited between October 2012 and February 2013. 200 (50%) were HIV positive. Median age was 42 years (range 16–83). Thirty-nine percent of patients were female. Median CD4 count in those with HIV was 415 cells/μL (range 0–1400). In total, 284 patients were re-surveyed between October 2014 and February 2015. Twenty-three (7.7%) of those resurveyed had raised Aspergillus -specific IgG levels. Twelve patients (4.2%) had CPA and 1 (0.4%) simple aspergilloma. A further three patients had a fungal ball on CT thorax, but normal levels of Aspergillus -specific IgG. HIV co-infection had no significant impact on the frequency of CPA. Three cases of recurrent pulmonary TB were identified, none in the CPA group. Conclusion: CPA complicates pulmonary tuberculosis. This data suggest the predicted global prevalence is accurate. This is a significant global public health problem, which is currently neglected. The clinical and radiological presentation of CPA is often identical to recurrent TB. In the absence of access to Aspergillus- specific IgG testing most cases of CPA are probably inaccurately diagnosed as recurrent 'smear-negative TB' and subjected to unnecessary and potentially toxic second-line TB therapy. Disclosures: I. Page, Astellas: Grant Investigator, Research grant. Siemens: Collaborator and Recipient of donated test kits for research purposes, Research support. Serion: Collaborator and Recipient of donated test kits for research purposes, Research support. Dynamiker: Collaborator and Recipient of donated test kits for research purposes, Research support. Genesis: Collaborator and Recipient of donated test kits for research purposes, Research support. M. Richardson, Astellas: Consultant, Consulting fee. Gilead: Consultant, Consulting fee. Dynamiker: Consultant, Consulting fee. MSD: Consultant, Consulting fee. Pfizer: Consultant, Consulting fee. Basilea: Consultant, Consulting fee. D. Denning, F2G: Shareholder, Shares. Astellas: Consultant, Consulting fee and Speaker honorarium. Sigma Tau: Consultant, Consulting fee. Basilea: Consultant, Consulting fee. Scynexis: Consultant, Consulting fee. Cidara: Consultant, Consulting fee. Biosergen: Consultant, Consulting fee. Quintiles: Consultant, Consulting fee. Pulmatrix: Consultant, Consulting fee. Pulmocide: Consultant, Consulting fee. Dynamiker: Speaker's Bureau, Speaker honorarium. Gilead: Speaker's Bureau, Speaker honorarium. Merck: Speaker's Bureau, Speaker honorarium. Pfizer: Speaker's Bureau, Speaker honorarium